A morphological model of Petropavlovskoe lode gold deposit (Polar Urals) - R Kh Mansurov (RUDN Journal of Engineering Research, 2011)
Key morphological features and quantitative parameters of mineralized structures which compose Petropavlovskoe lode gold deposit located in the northern part of the Voikar metallogenic unit are presented.